2022
DOI: 10.3390/agriculture12122070
|View full text |Cite
|
Sign up to set email alerts
|

Different Floor Management Systems Affect Soil Properties and Initial Development of Apple Tree (Malus × domestica Borkh.) in an Orchard

Abstract: In order to achieve sustainable food production, non-chemical weed management practices need to be developed for fruit growing. Tailor-made floor management systems enable efficient weed regulation, but they also affect the soil quality in an orchard. In this article, the effects of various floor management systems in a ‘Red Jonaprince’ apple (Malus × domestica Borkh.) orchard on the soil properties and the trees’ nutritional status and initial development during the first two years after the orchard’s establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…It has previously been well-documented that the floor management system affects the most important soil properties that decide its fertility [ 17 , 18 , 19 , 20 , 21 ]. The results published by Przybyłko et al [ 22 ] indicate that the dynamics and direction of changes that occur depend on the soil maintenance used. During three consecutive seasons of different floor management systems, use of the spent mushroom substrate led to an increase in the P, K, and Mg concentrations, as well as in the pH value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been well-documented that the floor management system affects the most important soil properties that decide its fertility [ 17 , 18 , 19 , 20 , 21 ]. The results published by Przybyłko et al [ 22 ] indicate that the dynamics and direction of changes that occur depend on the soil maintenance used. During three consecutive seasons of different floor management systems, use of the spent mushroom substrate led to an increase in the P, K, and Mg concentrations, as well as in the pH value.…”
Section: Discussionmentioning
confidence: 99%
“…During three consecutive seasons of different floor management systems, use of the spent mushroom substrate led to an increase in the P, K, and Mg concentrations, as well as in the pH value. On the other hand, Miscanthus straw showed to be a much poorer source of the analyzed macronutrients, although relatively high concentrations of P and K were noted in comparison to the systems tested where no organic litter was used at all [ 22 ]. The variations including increasing soil salinity and organic matter content after the spent mushroom application that we observed encouraged us to check to what extent the diversity of tree root-associated microbial communities was affected in such conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LMs seem to be effective in controlling weed growth, although they do not completely stop them [7][8][9][10]. The advantages of this method, emphasised by some authors, include the natural supplementation of the soil with nutrients due to the decomposition of cover plant tissues [11,12] and the improvement in the soil structure by cover plant roots, which creates a favourable environment for soil microorganisms [13]. Meta-analysis of data from Chinese orchards [14] showed that grass cover increased the microbial biomass carbon as well as abundances of bacteria, fungi, Agriculture 2023, 13, 2145 2 of 15 and actinobacteria by 47-78.7%, compared with orchards without grass cover.…”
Section: Introductionmentioning
confidence: 99%